Design of Sub‐Nanochannels between Graphene Oxide Sheets via Crown Ether Intercalation to Selectively Regulate Cation Permeation. Issue 8 (6th March 2020) - Bang, Ki Ryuk; Bahamon, Daniel; Vega, Lourdes F.; Cho, Eun Seon
Abstract: Graphene‐based membranes are a promising candidate for separating pollutants and ions. In particular, graphene oxide (GO) membranes are widely studied due to their unique nanochannels. The characteristic nanochannels of GO membranes can be manipulated via intercalation of cations, inhibiting the transport of other ions in the diffusion process. To maintain the tailored nanochannel during a pressure‐assisted filtration procedure, it is essential to retain such inserted cations. Here, dibenzo‐18‐Crown‐6 molecules (DB18C6) tightly binding to potassium ions are intercalated into GO nanosheets for preventing the leakage of the potassium ions from the nanochannel in the separation process. The complex between potassium ion and DB18C6 forges sub‐nanochannels between GO nanochannels, controlling the salt rejection rate as well as the permeation of water molecules, and selectively inhibiting the transport of Na + ions compared to the untreated GO membrane. The as‐prepared GO@Crown composite membranes exhibit excellent NaCl rejection rates (up to 60%), water permeance (3.11–8.86 LMH bar −1 ), and a Na + rejection rate (up to 62.5%) as well as an outstanding Na2 SO4 rejection rate (up to 88%) in the dead‐end filtration process. Molecular dynamics compute the tunable interlayer spacing of GO@Crown composite membranes and the possible configuration of crown ethers between GO layers, supporting the experimental results. Abstract : Interaction between cations and graphene oxide layers in a pressure‐assisted filtration process can be achieved by intercalating crown ether molecules between graphene oxide nanochannels. The intercalated crown ether molecules in nanochannels can bind with specific cations depending on the cavity size. The K + –dibenzo 18‐Crown‐6 complexes form sub‐nanochannels, which selectively regulates the transport of other cations, increasing the Na + rejection rate.